The convergence or divergence of design characteristics in determining the recall and persuasiveness of seaside destination slogans. (August 2022) - Qu, Ying; Dong, Yinyin; Xu, Feifei
Abstract: Current slogan design guidelines mainly focus on the unilateral effectiveness of the design characteristics (i.e., recall or persuasiveness). The underlying academic conjecture is that the recall and persuasiveness of slogans are driven by the same design characteristics. This study empirically tests the validity of this conjecture. We use slogans of China's seaside destinations and investigate the influences of eight design characteristics on the combined effects of recall and persuasiveness. The moderation of destination familiarity reveals that the driving characteristics of recall and persuasiveness converge to a certain extent in familiar destinations' slogans; but diverge substantially in unfamiliar destinations' slogans. The contributions of this study are twofold. From a theoretical perspective, verifying the conditional effects of important design characteristics prevents the separation of recall and persuasiveness in destination slogan research. From a managerial perspective, different methods of slogan design can be developed for familiar and unfamiliar destinations.